Comparative Bioavailability of Two Oral Formulations of Bromazepam in Healthy Volunteers - Lerner, Federico Ezequiel; Schere, Daniel; Batafarano, Nicolás; Casas, Florencio; Glancszpigel, Ricardo (Arzneimittelforschung, 2001)
The aim of this study was to assess the pharmacokinetic profile of two bromazepam (CAS 1812-30-2) formulations in 24 healthy volunteers. An open, randomised clinical trial designed as two-period crossover with 14-day washout between doses was employed. Plasma samples for assessments of their bromazepam concentration by HPLC-UV were obtained over 96 h after administration. No adverse effect was reported for any of the formulations administered. The following pharmacokinetics parameters were calculated: AUC(0–96h), AUCinf, Ke and T1/2. The 90 % confidence intervals (CI) for the mean test/reference individual ratios were 81–109 for AUC and 84–116 for Cmax. Since the 90 % CI for both, AUC and Cmax ratios were within the 80–125 % interval proposed by the Food and Drug Administration, it is concluded that the new bromazepam slow-release formulation is therapeutic equivalent to the conventional formulation for both, the extent and the rate of absorption after single dose administration in healthy volunteers.
Keywords: 1,4-Benzodiazepines; Bromazepam, bioavailability, clinical studies; CAS 1812-30-2